Ma-Minda starlikeness of certain analytic functions - JANANI, Baskar Babujee; RAVICHANDRAN, V. (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
A normalized analytic function defined on the open unit disc D is called Ma-Minda starlike if zf ′(z)/f(z) is subordinate to the function φ. For a normalized convex function f defined on D and α > 0, we determine the radius of Ma-Minda starlikeness of the function g defined as g(z) = (zf ′(z)/f(z))α f(z) for certain choices of φ. In particular, we investigate the radius of Janowski starlikeness of the function g. Mathematics Subject Classification (2010): 30C80, 30C45. Received 31 July 2023; Accepted 31 October 2023.